Online learning in the post-Covid-19 pandemic era: Is our higher education ready for it? - Hasan Djidu; Sufri Mashuri; Nasruddin Nasruddin; Andri Estining Sejati; Rasmuin Rasmuin; La Eru Ugi; Afudin La Arua (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2021)
This study aimed to describe the challenges of higher education in implementing online learning during the pandemic Covid-19 outbreak. This study was a qualitative research with a phenomenological approach. Data were collected from 408 students and 20 Lectures from 6 public universities and 6 private universities in Java, Sumatera, Kalimantan, Sulawesi, Nusa Tenggara, and Maluku, by filling out online questionaires and in-depth interviews via social media. The process of data analysis was data reduction, identifying themes, mapping interrelationships between themes, and concluding findings The results of data analysis showed that there were two main challenges, both for lecturers and students. First, limited resources, such as electronic devices (laptops/smartphones/others), learning resources, electricity, and internet connections. Second, lack of knowledge/skills on how to use the online learning media, finding and/or providing learning resources, managing online learning, providing online measuring tools, and carrying out online assessments. This condition has the greatest impact on students from low economic families, and who live in areas with limited access to learning facilities, such as electricity, and internet connections. Most of them lose learning opportunities because of these limitations.Â  Third, the difficulty of time management during the online learning period.